Colonial Records of the State of Georgia Volume 28, Part 2: Original Papers of Governor Wright, President Habersham, and Others, 1764-1782 - Hall, Leslie (Georgia Open History Library, 1979)
The Colonial Records of the State of Georgia document the colony through its first twenty-five years and includes correspondence between Georgia founder James Oglethorpe and the Trustees for Establishing the Colony, as well as records pertaining to land grants; agreements and interactions with Indigenous peoples; the settlement of a small Jewish community and the Salzburgers, German-speaking Protestant refugees; and the removal on restrictions of land tenure, rum, and slavery in the colony. Most of the local records of colonial Georgia were destroyed during the Revolution. Under Governor James Wright's direction, merchant John Graham loaded much of the official records on his vessel in the Savannah River. During the Battle of the Rice Boats in March 1776, the Inverness was burned while it lay at anchor. The destructive civil war that occurred in the latter phases of the Revolution resulted in further destruction. The Colonial Records of the State of Georgia, drawn from archival material in Great Britain, remain a unique source. Volume 28, Part II includes the papers of Governor James Wright, acting governor James Habersham, and others. The Georgia Open History Library has been made possible in part by a major grant from the National Endowment for the Humanities: Democracy demands wisdom. Any views, findings, conclusions, or recommendations expressed in this collection, do not necessarily represent those of the National Endowment for the Humanities.